Crisis, Policy Discourse, and Major Policy Change: Exploring the Role of Subsystem Polarization in Nuclear Energy Policymaking. (September 2015) - Rinscheid, Adrian
Abstract : Why do policy responses to one and the same event often vary so markedly between different jurisdictions? This contribution sheds light on conditions and processes that link crises to policy change or policy stability. Drawing on public policy theories and accounts from crisis management, the type of policy subsystem that is hit by a crisis is theorized to be a decisive factor when it comes to explaining variation in crisis‐induced policy reactions. The theoretical arguments are explored based on a comparative case study of Fukushima's differential impact on nuclear power policymaking in Japan and Germany. In order to systematically analyze interaction patterns of policy elites, the study capitalizes on recent methodological advances and applies a method called discourse network analysis. The analysis yields topographies of policy discourses around the Fukushima crisis in both countries and shows that crises can trigger major policy shifts when "anchors" for policy change—i.e., alternative policy ideas and proposals put forward by a minority coalition—are readily available. If a pre‐crisis subsystem is unitary, on the other hand, the pressure on incumbents is rather low and policy shifts are prevented from going beyond mere incremental adjustments..